Pengembangan Program Pembelajaran Berbasis Aktivitas pada Materi Momentum Impuls untuk Meningkatkan Keterampilan Berpikir Kritis Siswa (UPEJ Unnes Physics Education Journal, 2019)
Physics learning should optimize students' activities to practice critical thinking skills. But in practice learning has not yet facilitated the students to be able to think critically. Therefore, it is necessary to develop Activity Based Learning Program (PPBA) to improve students' critical thinking skill. This type of research is Research and Development with 4-D model, the procedure includes define, design, develop and disseminate. This research used three activity-based learning models that support the training of students’ critical thinking skills, the three models are PBL, NHT, PjBL. The sample in this research is four classes of MIA X in SMA Negeri 1 Bergas. Data taken in the form of students' critical thinking skills with indicators analyzing arguments, asking and answering questions, considering whether the source can be trusted or not, inducing and considering the results of induction, making and determining the results of consideration, identifying assumptions, determining an action, interacting with others. To obtain the data, instruments were used in the form of pretest, posttest, validation sheet of lesson plan, and questionnaire. The results of the data obtained were analyzed by prerequisite test, N-gain test, and average calculation. The analysis results show that PPBA is very feasible to use with the percentage of appraisal of 85.9% and can improve students' critical thinking skill with average N-gain factor 0.65 with medium category. The biggest increase was contributed by PBL model with N-gain factor of 0.66 with medium category. PPBA got high response with score 3.2 from maximum score 4. Based on the result of analysis it can be concluded that PPBA is feasible and can improve students' critical thinking